Prevalence of Human Papilloma Virus (HPV) during urine test and clinical examination at Teritip Health Center, East Balikpapan, East Kalimantan - Purwanti, Helti; Dzikri, Achmad; Wirapuspita Wisnuwardani, Ratih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Cervical cancer is primarily caused by Human Papillomavirus (HPV) infection, which is also a common cause of sexually transmitted diseases. HPV infection is present in 99.7% of cervical cancer cases. Globally, cervical cancer is the second most common cancer among women, while in Indonesia, it ranks as the highest. Teritip, an area in the eastern suburbs of Balikpapan city, is at high risk due to the mobility associated with the entry and exit of immigrant populations, which may increase HPV cases. Therefore, the author conducted this study. Objective : This study aimed to determine the frequency of Human Papillomavirus infection and to assess the relationship between age and HPV infection in adults and adolescents who underwent HPV DNA PCR testing and clinical evaluations at the Teritip Health Center, East Balikpapan, East Kalimantan, from December 2023 to June 2024. Research Methods/ Implementation Methods : A cross-sectional descriptive study was conducted to observe and collect data. A total of 180 patients underwent HPV PCR testing and clinical examination by a midwife. Results : Out of 180 participants, 6 were found to be infected with HPV. There was no statistically significant relationship between age and HPV infection Conclusion/Lesson Learned : There is no relationship between age and HPV infection. Therefore, regular HPV screening is necessary to ensure early detection and management